2009
DOI: 10.1038/nature08257
|View full text |Cite
|
Sign up to set email alerts
|

Global electromagnetic induction constraints on transition-zone water content variations

Abstract: Small amounts of water can significantly affect the physical properties of mantle materials, including lowering of the solidus, and reducing effective viscosity and seismic velocity. The amount and distribution of water within the mantle thus has profound implications for the dynamics and geochemical evolution of the Earth. Electrical conductivity is also highly sensitive to the presence of hydrogen in mantle minerals. The mantle transition zone minerals wadsleyite and ringwoodite in particular have high water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
239
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(268 citation statements)
references
References 40 publications
23
239
1
1
Order By: Relevance
“…It has been suggested that olivine, a primary mineral in the upper mantle, and its high-pressure polymorphs (wadsleyite and ringwoodite) could store a large amount of water (hydrogen ions) in their crystalline defects and act as a major water reservoir within Earth (2-4). Incorporation of water in these mantle minerals has been shown to influence their physical properties (5)(6)(7)(8)(9)(10)(11)(12) and the dynamics of the mantle and subducting slabs (13). In particular, water enrichment could influence the minerals' thermal transport properties, which, in turn, alters the temperature gradient in the mantle and subducting slabs.…”
mentioning
confidence: 99%
“…It has been suggested that olivine, a primary mineral in the upper mantle, and its high-pressure polymorphs (wadsleyite and ringwoodite) could store a large amount of water (hydrogen ions) in their crystalline defects and act as a major water reservoir within Earth (2-4). Incorporation of water in these mantle minerals has been shown to influence their physical properties (5)(6)(7)(8)(9)(10)(11)(12) and the dynamics of the mantle and subducting slabs (13). In particular, water enrichment could influence the minerals' thermal transport properties, which, in turn, alters the temperature gradient in the mantle and subducting slabs.…”
mentioning
confidence: 99%
“…Therefore, the structures and electronic properties of molten CO 2 predicted from the MD calculations have direct relevance to the lower mantle. For instance, electrical conductivity measured or inferred from geophysical studies provides important constraints on and understanding of the chemical and physical properties of the Earth's deep interior [Kelbert et al, 2009;Yoshino and Katsura, 2013]. It is generally accepted that the electrical conductivity in the Earth's mantle increases from 10…”
Section: Implications For Electrical Conductivities In Earth's Lower mentioning
confidence: 99%
“…The region between the Earth's surface and the ionosphere is generally current source-free, in which the magnetic field is conservative or curl-free and can thus be expressed as the gradient of a scalar potential (Lorrain and Corson 1970;Jackson 1998;Backus et al 1996;Sabaka et al 2010), known as potential magnetic field, as shown in equation (4).…”
Section: Separation Of Internal and External Fieldsmentioning
confidence: 99%
“…The induced magnetic disturbances from the Earth's interior sensed by geomagnetic observatories have been utilized to reveal mantle electrical conductivity structures since this method was implemented (e.g., Banks 1969; Schultz and Larsen 1990;Constable 1993;Olsen 1999;Kelbert et al 2009;Khan et al 2011). This technique has been valued as the most important method for studying mantle conductivity.…”
Section: Introductionmentioning
confidence: 99%